2006
DOI: 10.1021/jf052944j
|View full text |Cite
|
Sign up to set email alerts
|

Character Impact Odorants of Fennel Fruits and Fennel Tea

Abstract: The flavor of fennel fruits and fennel tea was examined by aroma extract dilution analysis of the respective dichloromethane extracts. In both fennel fruits and tea, trans-anethole, anisaldehyde, and trans-4,5-epoxy-2(E)-decenal showed high flavor dilution (FD) factors followed by fenchone, 1,8-cineole, (R)-alpha-pinene, estragole, and beta-myrcene. On the basis of these results, the odorants showing higher FD factors were quantified in tea as well as in fruits, and odor activity values (OAV) in tea were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…These values are defined by dividing the concentrations of the compound by its recognition threshold in a suitable matrix in Table 3 . For OAVs 1, an impact of the respective compound on the overall flavor can be assumed 23 . Among the aroma-active compounds of HD oil, geraniol 1139 , linalool 1058 , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These values are defined by dividing the concentrations of the compound by its recognition threshold in a suitable matrix in Table 3 . For OAVs 1, an impact of the respective compound on the overall flavor can be assumed 23 . Among the aroma-active compounds of HD oil, geraniol 1139 , linalool 1058 , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to extract the potent odorants of anise fruits, we chose a procedure similar to that reported recently. 5 Briefly, the volatiles were isolated by dichloromethane extraction followed by SAFE, which enables effective separation of the volatiles and minimizes the thermal impact on the sample. 13 The most odour-active compounds were then evaluated by AEDA, which gave the results shown in Table 2.…”
Section: Aroma Extract Dilution Analysis Of Anise Fruitsmentioning
confidence: 99%
“…Therefore, the question of the impact of estragole on the odour of other spices, such as anise and tarragon, has to be settled. 5 Anise (Pimpinella anisum) belongs to the family Apiaceae and is used as a herb in traditional dishes but also for medical and therapeutic purposes because of its digestive and sedative effects. A common use of anise is as a boiled infusion, while anise essential oil is utilized as a flavour additive in Turkish raki or Greek ouzo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soxhlet and accelerated solvent extraction (ASE) have been used for extraction of essential oil from Fennel (Rodríguez-Solana et al, 2014). Solvent extraction using dichloromethane has been reported for extraction of estragole in Fennel tea followed by GC-MS analysis (Zeller and Rychlik 2006). The effect of using different internal standards on the analytical method performance for estragole has been studied, results have concluded that using p-propyl anisole as an internal standard provided accurate results comparable to those obtained from other methods using stable isotopically labeled internal standard (Zeller et al, 2009).…”
Section: Introductionmentioning
confidence: 99%